Correction: Interactions of Prototype Foamy Virus Capsids with Host Cell Polo-Like Kinases Are Important for Efficient Viral DNA Integration. - Irena Zurnic; Sylvia Hütter; Ute Rzeha; Roger Helbig; Nicole Stanke; Juliane Reh; Erik Müllers; Martin V Hamann; Tobias Kern; Gesche K Gerresheim; Fabian Lindel; Erik Serrao; et al. (PLoS Pathogens)
[This corrects the article DOI: 10.1371/journal.ppat.1005860.].